2008
DOI: 10.1182/blood-2007-09-115451
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of sphingosine kinases 1 and 2 in human mast-cell functions

Abstract: Sphingosine-1-phosphate (S1P) is now emerging as a potent lipid mediator produced by mast cells that contributes to inflammatory and allergic responses. In contrast to its weak effect on degranulation of murine mast cells, S1P potently induced degranulation of the human LAD2 mast-cell line and cord blood-derived human mast cells (hMCs). S1P also stimulated production and secretion of cytokines, TNF-␣ and IL-6, and markedly enhanced secretion of a chemokine, CCL2/MCP-1, important modulators of inflammation. S1P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
128
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 33 publications
7
128
2
1
Order By: Relevance
“…Recently, it has been suggested that FcRI, activates both SphK1 and SphK2 to drive different responses in mouse and human mast cells (15,16). However, this is in contradiction with previous reports showing that SphK1 is activated by FcRI, and mediates proinflammatory responses, in rat, mouse, and human mast cells (11,13).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Recently, it has been suggested that FcRI, activates both SphK1 and SphK2 to drive different responses in mouse and human mast cells (15,16). However, this is in contradiction with previous reports showing that SphK1 is activated by FcRI, and mediates proinflammatory responses, in rat, mouse, and human mast cells (11,13).…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, a recent study, using mast cells-derived from SphK1 or SphK2 knockout (KO) mice, suggests that SphK2 is the isoform used by FcRI to mediate degranulation and cytokine and eicosanoids production (15). In contrast, a more recent study using small interfering RNA (siRNA) to silence the SPHK genes in human mast cells, shows that SphK1, but not SphK2, plays a critical role in Ag-induced degranulation migration and cytokine and eicosanoids production, with SphK2 playing a lesser role and only for the partial secretion of TNF-␣ (16). Thus, given the differences between silencing SPHK genes in wild-type cells and those cells where the kinases were deleted in the preimplantation embryo, it is possible that the differences observed are due to a compensatory mechanism during embryonic development of the KO mice and that SphK1 may indeed also be required for mouse mast cell degranulation and for the release of other proinflammatory mediators from murine mast cells in vitro and in vivo.…”
mentioning
confidence: 97%
“…Furthermore, S1P appears to be a promising target for the treatment of rheumatoid arthritis (as reviewed in [119]) and asthma [120]. Interestingly, in a study of murine collagen-induced arthritis model, two isoenzymes responsible for the production of S1P (sphingosine kinase 1 and sphingosine kinase 2) were shown to have distinct cellular functions [121].This surprising finding was also confirmed by other groups in different models [122][123][124]. In one of those studies, SphK1 and SphK2 were shown to have opposing functions for the regulation of ceramide biosynthesis [124].…”
Section: B) Sphingosine Derivatives: Sphingosine and S1psupporting
confidence: 70%
“…It is known from the literature that a deficiency of both sphingosine kinases, leads to embryonic lethality. However, no obvious phenotype is known in single knockout mice, indicating that apart from specific exceptions (Oskeritzian et al, 2008;Price et al, 2013) one enzyme may substitute the other (Alemany et al, 2007). The increased concentration of FTY720-P in the cytosol of the SphK1-deficient cells may thus be the result of a compensatory increase of SphK2 activity.…”
Section: Discussionmentioning
confidence: 99%